Foreseeability as a Determinant of Audit Responsibility. - Causey, Denzil Y. (The Accounting Review, 1973)
Abstract The article explores the concept of foreseeability as a determinant of the legal responsibility of auditors. Auditors have the ability to foresee that application of conservatism to avoid overstatement; elimination of disclaimers, qualifications and adverse opinions; and uniformity in application of accounting and auditing rules can limit users of financial statements to more realistic expectations. A balancing of the needs of users of financial reports for protection with the effect of imposing liability on auditors forms part of the question of auditor responsibility.